2012
DOI: 10.3136/fstr.18.263
|View full text |Cite
|
Sign up to set email alerts
|

Determination of γ-Aminobutyric Acid and Free Amino Acid Contents in Barley Seeds and Amounts Produced by Water Soaking Treatment

Abstract: The contents of γ-aminobutyric acid (GABA) and free amino acid in barley seeds, and the amounts produced by water soaking treatment, were determined. In decreasing order among wholemeal, Kankei n553, Kankei n554, Hiproly, Yonkei 9551, and Beau Fiber contained GABA at 41.7, 27.1, 24.5, 21.9, and 19.3 mg/100 g, respectively, and all had high lysine (lys) endosperm mutations. Yonkei 9551 (25.6 mg/100 g) with high lys gene lys1 and Yonkei 9552 (11.1 mg/100 g) with high lys gene lys3.a contained relatively large am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
2
1
0
1
Order By: Relevance
“…The mean value of GABA for the different barleys was 8.8 mg 100 -1 . This value agrees with that reported by Nogata et al [32] for different barley cultivars. These authors found that the average GABA content in barley samples without Lys mutation was 8 mg 100 g -1 .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The mean value of GABA for the different barleys was 8.8 mg 100 -1 . This value agrees with that reported by Nogata et al [32] for different barley cultivars. These authors found that the average GABA content in barley samples without Lys mutation was 8 mg 100 g -1 .…”
Section: Discussionsupporting
confidence: 94%
“…The mean free amino acid content value for the different barley cultivars was 276.5 mg 100 g -1 . Similar results were reported by Nogata et al [32] for different breeding line barleys, such as Kankei n553 (252.3 mg 100 g -1 ) and Kankei n554 (209.5 mg 100 g -1 ). On the other hand, the proportion of hydrophobic amino acids (Gly, Ala, Val, Leu, Ile, Met, Phe, and Pro) in barley was higher than those found for branched-chain amino acids or sulfur amino acids.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…(Received Dec. 22, 2015 ; Accepted Apr. 20,2016) 著者らは 1994 年,コメを水に漬けるとγ -アミノ酪酸 (GABA)が 急 激 に 生 成・蓄 積 す る こ と を 発 見 し た 1) . GABA は高等植物においては,ストレスに対する応答とし て,グルタミン酸脱炭酸酵素(GAD)の作用で,グルタミ ン酸からの 1 分子脱炭酸反応が起こることによって生成す る遊離アミノ酸である 2) ∼5) .哺乳動物においては,GABA は抑制系の神経伝達物質であり 6) ,経口投与によって高血圧 症を緩和させる 7) のみでなく,精神安定作用を有する事が 知られており 8) 9) ,その生理効果を期待して,チャ 10) やカボ…”
unclassified